Psychodynamic therapy and cognitive-behavioral therapy in social anxiety disorder: a multicenter randomized controlled trial - Leichsenring, Falk; Salzer, Simone; Beutel, Manfred E.; Herpertz, Stephan; Hiller, Wolfgang; Hoyer, Juergen; Hüsing, Johannes; Joraschky, Peter; Nolting, Bjoern; Poehlmann, Karin; Ritter, Viktoria; Stangier, Ulrich; et al. (The American journal of psychiatry, 2013)
Objective: Various approaches to cognitive-behavioral therapy (CBT) have been shown to be effective for social anxiety disorder. For psychodynamic therapy, evidence for efficacy in this disorder is scant. The authors tested the efficacy of psychodynamic therapy and CBT in social anxiety disorder in a multicenter randomized controlled trial. Method: In an outpatient setting, 495 patients with social anxiety disorder were randomly assigned to manual-guided CBT (N=209), manual-guided psychodynamic therapy (N=207), or a waiting list condition (N=79). Assessments were made at baseline and at end of treatment. Primary outcome measures were rates of remission and response, based on the Liebowitz Social Anxiety Scale applied by raters blind to group assignment. Several secondary measures were assessed as well. Results: Remission rates in the CBT, psychodynamic therapy, and waiting list groups were 36%, 26%, and 9%, respectively. Response rates were 60%, 52%, and 15%, respectively. CBT and psychodynamic therapy were significantly superior to waiting list for both remission and response. CBT was significantly superior to psychodynamic therapy for remission but not for response. Between-group effect sizes for remission and response were small. Secondary outcome measures showed significant differences in favor of CBT for measures of social phobia and interpersonal problems, but not for depression. Conclusions: CBT and psychodynamic therapy were both efficacious in treating social anxiety disorder, but there were significant differences in favor of CBT. For CBT, the response rate was comparable to rates reported in Swedish and German studies in recent years. For psychodynamic therapy, the response rate was comparable to rates reported for pharmacotherapy and cognitive-behavioral group therapy.